THE EFFECTIVENESS OF USING SPECIAL EXERCISES IN DEVELOPING THE STRENGTH AND PHYSICAL QUALITIES OF UPPER GRADE STUDENTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the effectiveness of applying specific exercises to develop the physical strength qualities of high school students. Physical strength plays a significant role in the development of adolescents, positively influencing their overall physical fitness and health. The study examines principles for selecting exercises that are tailored to students' age, physical abilities, and physiological characteristics. The findings provide recommendations aimed at promoting a healthy lifestyle and improving the effectiveness of physical education by enhancing strength development in high school students. This material is valuable for physical education teachers and coaches and can be applied within the sports-education system.